Allfinanz in Singapore : banks in insurance - Ho, Wai Yin (2014)
The main objectives of our study are to identify how banks are responding to the changing environment by selling insurance products in Singapore and to assess their experience in insurance. We hope that our findings will enable the banking and insurance industries to gain an insight into the development of this trend in Singapore.